In Vivo Efficacy of Bioagents and Fungitoxicants against False Smut Disease of Rice Caused by Ustilaginoidea virens (Cooke) Takahashi - Sachin Kumar; Ramji Singh; Durga Prasad (International Journal of Economic Plants)
The present experiment was conducted from June to November 2017 at Crop Research Center, Chirodi, Sardar Vallabhbhai Patel University of Agriculture & Technology, Meerut (U.P.), India to assess the efficacy of six fungicides-propiconazole, strobin, flutolanil, copper oxychloride, azoxystrobin, flusilazol, and two bioagents viz., Trichoderma harzianum and Pseudomonas fluorescens-against false smut of rice under natural epiphytotic field conditions. Once panicle emergence reached 50%, each fungicide and bioagent was sprayed once. The findings of present investigation revealed that spray of propiconazole @ 0.1% reduced the false smut significantly and resulted in the lowest percentage of infected tillers (7.48%) and smutted grains (4.98%) along with maximum yield parameters like number of tillers (294), 10-ears weight (30.10 g), 1000-grain weight (24.50 g) and yield (4903 kg ha-1); it was followed by the spray application of either azoxystrobin @ 0.07% or strobin @ 0.06% with above respective parameters. Apart from the fungicides applied, the application of Trichoderma harzianum also reduced the false smut and increased the yield components significantly over the control plots. However, the lowest 10-ear weight (22.80 g), 1000-grain weight (17.50g), and yield (3100 kg ha-1) along with the highest percentage of infected tillers (23.93%) and smutted grains (21.47%) were recorded in unprotected plots. Therefore, growers can be advised to use a foliar spray of one of three fungicides-propiconazole @ 0.1%, azoxystrobin @ 0.07%, or strobin @ 0.06%–at 50% panicle emergence stage to fungicidal control of false smut of rice.